Pengaruh Praktik Pengalaman Lapangan (PPL) dan Motivasi Belajar Terhadap Kompetensi Profesional Mahasiswa Pendidikan Ekonomi STKIP Pembangunan Indonesia - Irham Maulana Yunus; Muhammad Rakib; Harti Oktarina (Phinisi Integration Review, 2022)
This study aims to determine: the effect of field experience practice (PPL) and learning motivation on the professional competence of STKIP Pembangunan Indonesia's economic education students, either partially or simultaneously. This type of research is quantitative research with a total population of 152 students of economic education class 2018 who have participated in PPL. The sampling technique was done randomly (random sampling) with a sample of 110 students. The data collected were analyzed using multiple linear regression analysis techniques with the help of the SPSS program. The results of the analysis show that the practice of field experience (PPL) and learning motivation have a significant effect on the professional competence of students of STKIP Pembangunan Indonesia's economic education, either partially or simultaneously.